การประเมินประสิทธิภาพผลการประชาสัมพันธ์เรื่องระบบเตือนภัยสึนามิ - ชื่นนภา กัลยาพิเชฎฐ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
The objectives of this research were to study the strategies used and the effectiveness of communication of Tsunami warning system. Data were collected from documents, media products as well as interview of staff in department of National Disaster Warning Center. The effectiveness was also examined through exposure to information about, perception on, attitude toward the Tsunami warning system outcome were analyzed through 400 questionnaires collected from the Phuket inhabitants. The results of this research show that the principle strategies are to use mass media, specialized media, personal media and internet. Including to crisis management and risk communiation are another strategy that were used. The results of the study were as follows: 1) Most people in Phuket exposed at moderate level to Tsunami warning system information. People were exposed to television the most and perceive about the Tsunami warning system highly. People in effected area had neutral attitudes toward Tsunami warning system. 2) Exposure to media about Tsunami warning system were positively correlated with people s perception on this topic. 3) Exposure to media about Tsunami warning system were negatively correlated with people attitude toward this topic. 4) People s perception about Tsunami warning system was positively correlated with people attitude toward this topic.